Therapeutic Drug Monitoring of Cyclosporine Using Single Sampling Strategy - Duaa J. Al-Tamimi; Mays E. Alani; Afaq M. Ammoo; Jaafar J. Ibraheem (College of Pharmacy / Mustansiriyah University, 2020)
Cyclosporine is mainly used as Immunosuppressant after different kinds of transplantation including bone marrow, lungs, kidneys, liver, heart, and other types of organ transplantations. Immunosuppressants diminish organ rejection and elongate the survival of the transplanted organs. Due to the narrow therapeutic ranges and significantly high interindividual and intraindividual variability in blood levels of cyclosporine, there is essential and vital need of therapeutic drug monitoring (TDM) of this drug in order to maintain the patient within the required therapeutic concentrations, which consequently lead to optimizing the clinical outcome and decrease the hazard of toxicity or rejection following organ transplantations. The current review article was aimed to present data for using a single or possibly two blood sampling strategy to be used for TDM of cyclosporine in order to assess the optimal blood levels of cyclosporine used in organ transplant recipients. The results showed that steady state blood concentration of cyclosporine obtained after 2 hours (C2) and possibly after 3 hours (C3) of drug administration are the best sampling time points which reflect total drug exposure (area under blood concentration versus time curve=AUC) and consequently reflecting the effect and the adverse effect(s) of cyclosporine. On the other hand, blood samples obtained at other time points particularly steady state trough concentration obtained before the next dose (C0) demonstrated poor correlation with total drug exposure and consequently the clinical outcome of the drug. Moreover, this study also demonstrated that for organs transplantations TDM of cyclosporine and assessing the clinical conditions of the patients should be routinely performed in order to adjust the dose to get optimal effect and to diminish the adverse effects of the drug. This review article focused on the findings which indicated that monitoring steady-state blood levels of cyclosporine after 2 hours (C2) and likely after 3 hours (C3) of drug intake may be used as ideal surrogate index in TDM of cyclosporine and for predicting the clinical outcome of the drug in all and different types of organs transplantations.